2019
DOI: 10.1371/journal.pone.0219785
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography angiography of superficial retinal vessel density and foveal avascular zone in myopic children

Abstract: Purpose To assess the superficial retinal vessel density (SRVD) and foveal avascular zone (FAZ) in myopic children using optical coherence tomography angiography (OCTA). Methods 174 eyes of 89 subjects with myopia and 101 eyes of 54 age-matched, emmetropic volunteers (control group) were enrolled in this study. The mean age of the subjects and controls was 13.9 (SD ± 2.3) and 13.1 (SD ± 2.4), respectively. Myopia was defined as spherical equivalent <– 1.0 diopter. Emmet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 24 publications
8
47
2
1
Order By: Relevance
“…Several reports have investigated the FAZ in myopic eyes. 5,[14][15][16]21,22 Sung et al reported lower peripapillary vessel density and larger super cial and deep FAZ areas in highly myopic eyes, as elucidated using OCTA. 5 He et al also demonstrated that reduced radial peripapillary capillary, deep parafoveal vessel density, and enlarged FAZ area occurred in high myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have investigated the FAZ in myopic eyes. 5,[14][15][16]21,22 Sung et al reported lower peripapillary vessel density and larger super cial and deep FAZ areas in highly myopic eyes, as elucidated using OCTA. 5 He et al also demonstrated that reduced radial peripapillary capillary, deep parafoveal vessel density, and enlarged FAZ area occurred in high myopia.…”
Section: Discussionmentioning
confidence: 99%
“…Gołębiewska et al [30] studied the foveal microvasculature and found that the FAZ area was larger in myopic eyes than in the control group. However, studies by Leng et al [31] and Ucaket al [32] showed no difference in FAZ area in both high and low myopic eyes.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In another publication, they found an increase in the FAZ field in myopic children compared to the control group. 23 In studies conducted with changes in FAZ perimetry, AI, and FD, it has been shown that there may be differences in the early stages of the disease even in the preclinical stages. 24 In their study in diabetic children, it is shown that FAZ perimeter, AI, and FD change without retinopathy findings.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 In another publication, they found an increase in the FAZ field in myopic children compared to the control group. 23…”
Section: Discussionmentioning
confidence: 99%